2010
DOI: 10.1111/j.1365-263x.2010.01044.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of 3Mix and Vitapex® as treatment options for pulpally involved primary molars

Abstract: 3Mix and Vitapex((R)) can be used as a root canal treatment agent in pulpally involved primary teeth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
135
5
9

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(166 citation statements)
references
References 11 publications
17
135
5
9
Order By: Relevance
“…After 6 months, clinical and radiographic success rates in the ES (90.5 and 85.7%, respectively) and C groups (88.9 and 72.2%, respectively) were comparable to those observed in previous studies, which have reported clinical success rates of 96 to 100% and radiographic success rates of 76 to 84% during 6 to 22.6 months of follow-up 6,8,11,18) . Trairatvorakul and Detsomboonrat (2012) reported clinical and radiographic success rates to be 94.9 and 54.4%, respectively, at a 6-month follow-up 19) .…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…After 6 months, clinical and radiographic success rates in the ES (90.5 and 85.7%, respectively) and C groups (88.9 and 72.2%, respectively) were comparable to those observed in previous studies, which have reported clinical success rates of 96 to 100% and radiographic success rates of 76 to 84% during 6 to 22.6 months of follow-up 6,8,11,18) . Trairatvorakul and Detsomboonrat (2012) reported clinical and radiographic success rates to be 94.9 and 54.4%, respectively, at a 6-month follow-up 19) .…”
Section: Discussionsupporting
confidence: 77%
“…Nakornchai et al (2010) reported no pathologic mobility, whereas Trairatvorakul and Detsomboonrat (2012) noted that 6.6% of patients showed pathologic mobility 8,19) . At a 2-year follow-up, Kargul et al (2010) reported that 4.6% of patients presented with pathologic mobility 5) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Propylene glycol and polyethylene glycol have also been used as vehicles in the preparation of 3 Mix, which is a mixture of 3 types of antibiotics and has been used to treat pulpally involved primary molars. Propylene glycol and polyethylene glycol serves as good drug delivery system because of its biocompatibility, ease in manipulation, and handling [12] . In the study, propylene glycol and polyethylene glycol combination did not exhibit any microbial inhibitory effects of its own.…”
Section: Discussionmentioning
confidence: 99%
“…Os poucos estudos existentes para o tratamento endodôntico radical abordam o efeito de materiais obturadores e irrigantes dentro do canal (Mortazavi;Mesbahi, 2004;Cerqueira et al, 2008;Nakornchai et al, 2010). A técnica endodôntica completa detalhada acaba deixando de ser aprofundada, e os diferentes passos técnicos que poderiam aperfeiçoar esse tipo de conduta terapêutica são ainda poucos explorados.…”
Section: Endodontia Em Dentes Decíduosunclassified